Antecedents and Consequences of Job Stress among Private Sector Employees in Saudi Arabia - Abaalhasan, Ahad; Nassani, Abdelmohsen (The Arab Journal of Administration, 2023)
This study’s main goal is to investigate the consequences that is resulted from job stress in Saudi Arabia firms. More precisely, the privet sector. It analyzes and explains common job stresses such as job burnout, role ambiguity and how it can lead to the turnover intention. The study sample consisted of 402 respondents, and the data was collected using an online questionnaire. Statical procedures were applied via SPSS (means, standard deviation, correlation analysis, reliability analysis) and AMOS (path analysis). Results of this research study have concluded that job stress has an indirect effect on turnover intention; however, job burnout directs the effect which means that when employees are in stress, it leads to job burnout, which may increase and so their turnover may increase. The generalizability of the research findings might be constrained because of the research approach and the technique of sampling used. Researchers are thus urged to dig deeper into the offered premises. Practical consequences. The study analyzes the effects on the setting of the development workplace. This study addresses an acknowledged demand by investigating how to decrease the turnover intention and study need by investigating how to decrease the turnover intention and study reasons behind job stress and unhealthy work environment.